THE EFFECT OF INQUIRY-BASED SCIENCE TEACHING APPROACH ON SELF- CONCEPT OF SECONDARY SCHOOL PHYSICS STUDENTS IN KITUI COUNTY, KENYA - Gathage , John; Embeywa, Henry; Koech, Peter (African Journal of Education and Practice, 2021)
Purpose: The study sought to investigate the effect of Inquiry-Based Science Teaching Approach on learners' self-concept of secondary school physics students in Kitui County, Kenya. Methodology: The study adapted Quasi Experimental Research Design and in particular the Solomon's Four Non-Equivalent Control Group Research Design. The target population of the study was 1600 form four Physics students from 40 Extra-County secondary schools in Kitui County. Stratified random sampling was used to select four Extra-County schools (2 Girls and 2 Boys). Purposive sampling was used to select 40 students from each of the four schools and a Physics teacher from each of the two sampled schools; giving a sample size of 160. A students' questionnaire on self- concept was the research instrument. A reliability coefficient of 0.776 was obtained. Both descriptive and inferential data were analysed. The descriptive analysis was by means of frequencies, means, standard deviation and percentages. Inferential analysis was through Analysis of Variance, Chi-square and the Least Significant Difference (LSD) technique at a significance level of coefficient alpha Î±=0.05. Findings: The results showed a statistically significant difference in self-concept between students taught using IBSTA and those taught by the conventional methods. The study established that out of the four indicators of self-concept, only role performance was not statistically significant. Consequently, the study concludes that IBSTA is effective in improving students' self-concept. Unique contribution to theory, practice and policy: The theories were validated in that there was knowledge was actively constructed and need to prepare a learner to have a self -concept after learning. The researcher recommended that creation of an enabling environment for IBSTA be adopted in schools, an appropriate policy should be developed for diploma colleges and universities to train their teacher trainees with an emphasis on IBSTA as part of their Physics training curriculum and KICD should introduce and develop a programme for the Induction and Mentorship of Physics Teachers on the implementation of IBSTA so as to empower them with inquiry skills.